UNDERSTANDING VOLATILITY IN FINANCIAL MARKETS: A ROADMAP FOR RISK MANAGEMENT AND OPPORTUNITY IDENTIFICATION (International Journal of Innovative Technologies in Economy, 2024)
Volatility in financial markets has long been recognized as a crucial metric for risk management and opportunity assessment. This paper explores the significance of volatility as a key indicator in financial markets, its role in managing risk, and its potential as a roadmap for identifying opportunities and challenges. Drawing upon an extensive literature review and quantitative analysis, we delve into various aspects of volatility, including its measurement, implications, and applications. The methodology encompasses a comprehensive examination of historical market data, employing standard deviation and GARCH models to estimate volatility measures. The findings highlight the importance of understanding volatility dynamics for effective decision-making in financial markets. Key results include the identification of volatility clustering behavior, the significance of implied volatility in reflecting market sentiment, and the critical role of volatility in risk management and asset allocation. The discussion emphasizes the theoretical and practical implications of the research, offering valuable insights for investors, policymakers, and researchers. This study contributes to the ongoing discourse on volatility in financial markets, providing a robust framework for navigating the complexities of market dynamics and identifying potential opportunities amidst uncertainty.